Future horizons in diabetes treatment: hypoglycemic activity of [1,2,4]triazino[2,3-c]quinazoline derivatives - Trzhetsynskyi, Serhii; Nosulenko, Inna; Kinichenko, Anna; Skoryna, Dmytro; Berest, Halyna; Shvets, Volodymyr; Voskoboinik, Oleksii; Kovalenko, Serhii; Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus (T2DM) remains a significant and multifaceted challenge for modern healthcare. This issue becomes even more pressing during times of armed conflict and the subsequent recovery period, as research indicates an increased incidence of T2DM among combat veterans, largely due to post-traumatic stress disorder. Although numerous antidiabetic drugs are currently available, achieving optimal control of hyperglycemia continues to be problematic. In this context, and as part of a focused search for biologically active substances within the class of substituted and condensed [1,2,4]triazino[2,3-c]quinazolines, we explored the hypoglycemic effects of a newly synthesized series of such compounds. The study involved 21 synthesized compounds bearing the [1,2,4]triazino[2,3-c]quinazoline core. Experiments were conducted using white Wistar rats weighing between 260 and 280 grams. Prescreening of hypoglycemic activity was evaluated based on changes in blood glucose levels before and after compound administration by rats with normoglycemia. Compounds that demonstrated the most pronounced activity were selected for extended pharmacological evaluation using oral glucose tolerance test, adrenaline test, and rapid insulin tests in rats with dexamethasone-induced insulin resistance. Initial pharmacological screening under normoglycemic conditions showed that seven studied compounds significantly lowered blood glucose levels. Follow-up investigations validated the high hypoglycemic effect of 1,2,2-trimethyl-3-(3-methyl-2-oxo-2H- [1,2,4]triazino[2,3-c]quinazolin-6-yl)cyclopentane-1-carboxylic acid. Among the tested substances, compound 3-phenyl-6-(phenylamino)-2H-[1,2,4]triazino[2,3-c]quinazolin-2-one was the only one to exhibit moderate activity in the adrenaline tolerance test. None of the compounds enhanced insulin sensitivity in the liver or peripheral tissues. The findings suggest that substituted [1,2,4]triazino[2,3-c]quinazolines constitute a promising scaffold for the development of new hypoglycemic agents. 11β-Hydroxysteroid dehydrogenase is the most likely molecular target for lead-compound 1,2,2-trimethyl-3-(3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)cyclopentane-1-carboxylic acid.